Characterization of Microchannel Replicability of Injection Molded Electrophoresis Microfluidic Chips - Jiang, Bingyan (Polymers (Basel), 2019)
Microfluidic chips have been widely applied in biochemical analysis, DNA sequencing, and disease diagnosis due to their advantages of miniaturization, low consumption, rapid analysis, and automation. Injection molded microfluidic chips have attracted great attention because of their short processing time, low cost, and mass production. The microchannel is the critical element of a microfluidic chip, and thus the microchannel replicability directly affects the performance of the microfluidic chip. In the current paper, a new method is proposed to evaluate the replicability of the microchannel profile via the root mean square value of the actual profile curve and the ideal profile curve of the microchannel. To investigate the effects of injection molding parameters (i.e., mold temperature, melting temperature, holding pressure, holding time, and injection rate) on microchannel replicability, a series of single-factor experiments were carried out. The results showed that, within the investigated experimental range, the increase of mold temperature, melt temperature, holding pressure, holding time, and injection rate could improve microchannel replicability accuracy. Specifically, the microchannels along the flow direction of the polymer melt were significantly affected by the mold temperature and melt temperature. Moreover, the replicability of the microchannel was influenced by the distance from the injection gate. The effect of microchannel replication on electrophoresis was demonstrated by a protein electrophoresis experiment.